PERAN DIPLOMASI PADA PEPERANGAN SEBAGAI UPAYA MEMPERTAHANKAN KEKUASAAN DALAM SERAT LOKAPALA - Ni’mawati, Mufidatun (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study examines the crucial role of diplomacy in the context of warfare as a strategy for maintaining power in the ancient Javanese literary work Serat Lokapala. Diplomacy is positioned not merely as a tool for conflict resolution, but as an integral strategy for preserving the stability of state power. The aim of this research is to identify the forms of diplomacy presented in the text and to analyze their strategic roles. The study employs a descriptive qualitative method, using philological and postcolonial theory approaches, particularly that of Robert J.C. Young. Data were collected through literature review of the Serat Lokapala manuscript and related academic references. The findings reveal two main forms of diplomacy: musyawarah (deliberation) as strategic negotiation and nyantri (spiritual apprenticeship) as a form of spiritual diplomacy. Both forms play a vital role in maintaining authority, strengthening internal solidarity, and preventing defeat in warfare. The discussion emphasizes that the values of diplomacy found in this traditional text remain relevant to contemporary diplomatic practices, especially in efforts to resolve conflicts peacefully and ethically. In conclusion, diplomacy in Serat Lokapala is a key element in constructing a defense strategy that integrates rational, moral, and spiritual aspects. ABSTRAK Penelitian ini mengkaji pentingnya peran diplomasi dalam konteks peperangan sebagai strategi mempertahankan kekuasaan dalam karya sastra Jawa kuno Serat Lokapala. Diplomasi diposisikan bukan sekadar alat penyelesaian konflik, melainkan sebagai strategi integral dalam menjaga stabilitas kekuasaan negara. Tujuan penelitian ini adalah untuk mengidentifikasi bentuk-bentuk diplomasi yang muncul dalam teks serta menganalisis peran strategisnya. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan teori filologi dan poskolonialisme Robert J.C. Young. Data dikumpulkan melalui studi pustaka terhadap naskah Serat Lokapala dan referensi ilmiah terkait. Hasil penelitian menunjukkan dua bentuk utama diplomasi: musyawarah sebagai perundingan strategis dan nyantri atau berguru sebagai bentuk diplomasi spiritual. Kedua bentuk ini memainkan peran penting dalam menjaga kekuasaan, memperkuat solidaritas internal, dan mencegah kekalahan dalam peperangan. Diskusi menegaskan bahwa nilai-nilai diplomasi dalam teks tradisional tersebut tetap relevan dengan praktik diplomasi kontemporer, khususnya dalam upaya penyelesaian konflik secara damai dan beretika. Kesimpulannya, diplomasi dalam Serat Lokapala merupakan elemen kunci dalam membangun strategi pertahanan yang menggabungkan aspek rasional, moral, dan spiritual.